Cocaine induces astrocytosis through ER stress-mediated activation of autophagy. Issue 8 (2nd August 2016) - Periyasamy, Palsamy; Guo, Ming-Lei; Buch, Shilpa
ABSTRACT: Cocaine is known to induce inflammation, thereby contributing in part, to the pathogenesis of neurodegeneration. A recent study from our lab has revealed a link between macroautophagy/autophagy and microglial activation. The current study was aimed at investigating whether cocaine could also mediate activation of astrocytes and, whether this process involved induction of autophagy. Our findings demonstrated that cocaine mediated the activation of astrocytes by altering the levels of autophagy markers, such as BECN1, ATG5, MAP1LC3B-II, and SQSTM1 in both human A172 astrocytoma cells and primary human astrocytes. Furthermore, cocaine treatment resulted in increased formation of endogenous MAP1LC3B puncta in human astrocytes. Additionally, astrocytes transfected with the GFP-MAP1LC3B plasmid also demonstrated cocaine-mediated upregulation of the green fluorescent MAP1LC3B puncta. Cocaine-mediated induction of autophagy involved upstream activation of ER stress proteins such as EIF2AK3, ERN1, ATF6 since blockage of autophagy using either pharmacological or gene-silencing approaches, had no effect on cocaine-mediated induction of ER stress. Using both pharmacological and gene-silencing approaches to block either ER stress or autophagy, our findings demonstrated that cocaine-induced activation of astrocytes (measured by increased levels of GFAP) involved sequential activation of ER stress and autophagy. Cocaine-mediated-increased upregulation of GFAP correlated with increased expression of proinflammatory mediators such as TNF, IL1B, and IL6. In conclusion, these findings reveal an association between ER stress-mediated autophagy and astrogliosis in cocaine-treated astrocytes. Intervention of ER stress and/or autophagy signaling would thus be promising therapeutic targets for abrogating cocaine-mediated neuroinflammation.